2019
DOI: 10.1111/ijpp.12557
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to pharmacist prescribing: a scoping review comparing the UK, New Zealand, Canadian and Australian experiences

Abstract: Objectives Non‐medical prescribers, including pharmacists, have been found to achieve comparable clinical outcomes with doctors for certain health conditions. Legislation supporting pharmacist prescribing (PP) has been implemented in the United Kingdom (UK), Canada and New Zealand (NZ); however, to date, Australian pharmacists have not been extended prescribing rights. The purpose of this review was to describe the barriers to PP found in the literature from the UK, Canada, NZ and Australia, and examine the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 88 publications
2
59
0
3
Order By: Relevance
“…Many barriers to pharmacist prescribing exist. A scoping review of these barriers by Zhou et al [55] revealed three key themes that should be factored in to the current debate: (1) the socio-political context; (2) resourcing issues; and (3) prescriber competence. We advocate for the ongoing exploration of the expansion of the peri-operative pharmacists and nurses’ role in prescribing and collaborative partnered charting models.…”
Section: Discussionmentioning
confidence: 99%
“…Many barriers to pharmacist prescribing exist. A scoping review of these barriers by Zhou et al [55] revealed three key themes that should be factored in to the current debate: (1) the socio-political context; (2) resourcing issues; and (3) prescriber competence. We advocate for the ongoing exploration of the expansion of the peri-operative pharmacists and nurses’ role in prescribing and collaborative partnered charting models.…”
Section: Discussionmentioning
confidence: 99%
“…Research has captured Canadian pharmacists’ apprehension about their expanding role related to uncertainty around remuneration, perceived physician skepticism about pharmacists’ skills, and pharmacists’ access to comprehensive patient health records. 35 , 77 , 78 Pharmacists have expressed a need for continuing professional development and education delivered in innovative models that are tailored to the site of practice and learners’ unique needs. 79 Conversely, factors that may make pharmacists feel more comfortable and confident assuming new roles and responsibilities in the primary health care system, consequently facilitating practice change, are summarized by Gregory et al with the “9 Ps of practice change” mnemonic: permission, process pointers, practice/rehearsal, positive reinforcement, personalized attention, peer referencing, physician acceptance, patients’ expectations, professional identity, and payment.…”
Section: Toward Primary Health Care Integration and Reformmentioning
confidence: 99%
“…4,5 The pharmacists' expanded deprescribing role can be achievable with a teambased approach in which there is a clear delineation of roles and responsibilities, separating the prescribing from the dispensing pharmacist, as in New Zealand. 5,6 In Australia, many health practitioners can prescribe medications. For example, nurse practitioners can initiate and deprescribe within the boundaries of legislation and scope; that is, limited by the scope of practice, requirements from the Medicare Benefits Schedule and the Pharmaceutical Benefits Scheme, and by relevant hospital formulary or prescribing arrangements.…”
Section: Deprescribing Needs To Be Considered In the Pharmacists' Prementioning
confidence: 99%
“…The pharmacists’ expanded deprescribing role can be achievable with a team‐based approach in which there is a clear delineation of roles and responsibilities, separating the prescribing from the dispensing pharmacist, as in New Zealand . In Australia, many health practitioners can prescribe medications.…”
mentioning
confidence: 99%